2016
DOI: 10.1186/s12978-016-0209-x
|View full text |Cite
|
Sign up to set email alerts
|

Attitudes towards human papillomavirus vaccination among African parents in a city in the north of England: a qualitative study

Abstract: BackgroundHuman papillomavirus (HPV) is sexually transmitted and has been conclusively linked to cervical cancer and genital warts. Cervical cancer is attributed to approximately 1100 deaths annually in UK, and is the second most common female cancer globally. It has been suggested that black African women are more predisposed to HPV infection and cervical cancer. A vaccine has been developed to reduce HPV infection, and in the UK, has been offered to 12–13 year old adolescent girls through schools as part of … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
66
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 50 publications
(68 citation statements)
references
References 45 publications
2
66
0
Order By: Relevance
“…25,37,71 Concerns about side effects were particularly prevalent among hesitant participants from studies in the Netherlands (2009-2011, 69%), 26,28 Romania (2010, 60%), 79 and Greece (2005-2014, 54%). 31,34,40,42,78 Qualitative results Almost all qualitative articles described concerns about potential side effects of HPV vaccination, [52][53][54][55][56][57]59,60,62,64,66,69,[98][99][100][101][102][103][104][105][106][107] often described as fears of long-term side effects not yet identified through trials. 54,55,59,60,62,64,66,69,81,[98][99][100][101][102][103]…”
Section: Quantitative Resultsmentioning
confidence: 99%
“…25,37,71 Concerns about side effects were particularly prevalent among hesitant participants from studies in the Netherlands (2009-2011, 69%), 26,28 Romania (2010, 60%), 79 and Greece (2005-2014, 54%). 31,34,40,42,78 Qualitative results Almost all qualitative articles described concerns about potential side effects of HPV vaccination, [52][53][54][55][56][57]59,60,62,64,66,69,[98][99][100][101][102][103][104][105][106][107] often described as fears of long-term side effects not yet identified through trials. 54,55,59,60,62,64,66,69,81,[98][99][100][101][102][103]…”
Section: Quantitative Resultsmentioning
confidence: 99%
“…Twelve studies were conducted in the USA, three in the UK, one in the Netherlands, one in Denmark, one in Sweden, and one in Puerto Rico. Six studies were conducted in community organizations including faith-based centres like churches and mosques [21][22][23][24][25][26], eight in health and social service agencies [27][28][29][30][31][32][33][34], two in schools and/or community groups [35,36], another two in social clubs [37,38], and one in a household [39].…”
Section: Resultsmentioning
confidence: 99%
“…Of the 19 studies, 16 reported on knowledge of the immigrant parents about HPV vaccine (Table 2), 13 reported their attitudes (Table 3) and 10 recorded perceptions (as defined by study author) towards HPV vaccine (Table 4). Four studies reported knowledge and attitudes [21,27,30,37] and one reported knowledge and perceptions [26], seven studies reported on all three outcomes (knowledge, attitude and perceptions) [22,23,29,35,36,38,39].…”
Section: Resultsmentioning
confidence: 99%
“…The current trend suggests a relatively low level of awareness on HPV-associated diseases in males and acceptability of vaccination against the virus in most countries but worst in developing nations [75][76][77][78][79]. There are efforts from varying perspectives by different groups to improve the current situation based on findings from some studies [80,81].…”
Section: Future Perspectives On Hpv In Malesmentioning
confidence: 99%